2021
DOI: 10.12982/vis.2022.012
|View full text |Cite
|
Sign up to set email alerts
|

Production performance and egg quality evaluation of indigenous chickens across different agro-ecologies of Southern Ethiopia

Abstract: Indigenous chickens were evaluated for their egg production, growth performances, and external and internal egg quality parameters across three agro-ecologies. For experiment 540 (180 male and 432 female) chickens were distributed to the three agro-ecologies (lowland, midland, and highland) at their 20 weeks age. Body weight was recorded from each chicken during distribution, 4th week, and 8th week after distribution into pre-selected households. Egg production potential was identified from the indigenous chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
2
8
1
Order By: Relevance
“…In agreement with this result, [43] reported significant difference in egg shell weight of chicken eggs for different agro ecology for farmer managed chicken. However, it was different from the finding of [44] who reported uniform egg shell weight in different agro ecology of southern Ethiopia.…”
Section: Opportunities Chicken Productioncontrasting
confidence: 99%
“…In agreement with this result, [43] reported significant difference in egg shell weight of chicken eggs for different agro ecology for farmer managed chicken. However, it was different from the finding of [44] who reported uniform egg shell weight in different agro ecology of southern Ethiopia.…”
Section: Opportunities Chicken Productioncontrasting
confidence: 99%
“…Thai native chickens (Pradu Hangdum) produced 117 eggs per year (Mookprom et al, 2017). Egg production of indigenous chickens across different agro-ecologies of Ethiopia was 51.40 eggs/hen/ year, with egg weight 48.60 g (Bekele et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Its natural presentation or disposition appeals to people of all ages and classes; however, the major drawback in egg production and consumption is its rapid deterioration, leaving it offensive. Bekele et al (2022) listed the factors that affect egg quality deterioration to include variation in environment, the composition of feed, and management practices of the hen. Rizzi (2020) reported that genotype and age affect most egg quality traits, and Goto et al (2022), working with Japanese quail and Brown layer chickens, observed genotype effect on the amino acids contents of egg yolk and albumen.…”
Section: Introductionmentioning
confidence: 99%
“…According to Bekele et al (2022), egg weight correlates positively with egg length and breadth. However, Okonkwo (2014) and Sadaf et al (2021) reported little or no genetic correlation between egg quality traits, and the relationship remains fairly constant even as laying age progressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation